Art therapy in expressing emotions and managing stress among students: interactive approach - Haryati, Asti; Hamzah, Syukri; Dharmayana, I Wayan (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This study examines the effectiveness of Art Therapy as an intervention in managing stress and expressing emotions in students. By using the mixed methods method, the research population was carried out on 3rd Semester Guidance and Counseling students at UIN Fatmawati Sukarno Bengkulu, totaling 92 people. And the research sample used in the experimental group and control group was 20 people. this study involved experimental groups that received art therapy sessions and control groups that did not receive interventions. Stress and emotional scale are measured before and after intervention. The results show that the experimental group experienced a significant decrease in stress levels and increased emotional control compared to the control group. Art Therapy has proven to be an effective approach to improving students' mental well-being, providing self-expression media, and supporting stress management. These findings highlight the potential integration of art therapy in university counselling services to support student mental health.